Rancang Bangun Sistem Manajemen Aset Berbasis RFID dengan Penentuan Prioritas Pemeliharaan Menggunakan Fuzzy-MARCOS: (Studi Kasus: Bidang TIK Polda Sumatera Barat) - Muhammad Fatieh Akram Faritshi; Ahmaddul Hadi; Denny Kurniadi; Randi Proska Sandra (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2026)
The management of State-Owned Assets (Barang Milik Negara/BMN) at the ICT Division of the West Sumatra Regional Police faces three fundamental challenges: reliance on error-prone manual recording, data inconsistencies between official government systems (SAKTI and SIMAN) and actual field conditions, and the absence of an objective mechanism for determining asset maintenance priorities. This study designs and develops a web-based asset management system integrating Radio Frequency Identification (RFID) Portable Handheld Reader technology with the Fuzzy-MARCOS (Measurement Alternatives and Ranking according to Compromise Solution) method as a Decision Support System (DSS) for multi-criteria maintenance prioritization, developed using the Prototype methodology with Laravel and React frameworks. The results demonstrate that the system successfully automates real-time asset location tracking through RFID integration, improves the efficiency of asset data management, generates accurate maintenance priority scores via the Fuzzy-MARCOS algorithm with zero deviation from manual calculations, and achieves a 100% functional success rate across all system modules. The integration of RFID Handheld technology and Fuzzy-MARCOS within a single unified platform for government BMN asset management constitutes the novelty of this study, with strong potential as a digital asset governance model supporting e-government implementation in law enforcement institutions.